2011
DOI: 10.1371/journal.pone.0017948
|View full text |Cite
|
Sign up to set email alerts
|

BRAF V600E Mutations Are Common in Pleomorphic Xanthoastrocytoma: Diagnostic and Therapeutic Implications

Abstract: Pleomorphic xanthoastrocytoma (PXA) is low-grade glial neoplasm principally affecting children and young adults. Approximately 40% of PXA are reported to recur within 10 years of primary resection. Upon recurrence, patients receive radiation therapy and conventional chemotherapeutics designed for high-grade gliomas. Genetic changes that can be targeted by selective therapeutics have not been extensively evaluated in PXA and ancillary diagnostic tests to help discriminate PXA from other pleomorphic and often mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
204
1
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 274 publications
(219 citation statements)
references
References 52 publications
9
204
1
5
Order By: Relevance
“…Total or partial responses of PXAs to these therapies have been reported. 4 Two independent studies have reported a high frequency of BRAF mutation in PXA (60%-66%), 5,23 and Dougherty et al 6 also explored GG and pilocytic astrocytoma, finding 18% and 9% of these lesions, respectively, with BRAF mutations. Moreover, a common origin for these 3 tumors has been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Total or partial responses of PXAs to these therapies have been reported. 4 Two independent studies have reported a high frequency of BRAF mutation in PXA (60%-66%), 5,23 and Dougherty et al 6 also explored GG and pilocytic astrocytoma, finding 18% and 9% of these lesions, respectively, with BRAF mutations. Moreover, a common origin for these 3 tumors has been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Together with other identified fusion events such as SRGAP3:RAF1 ), RAF fusion events occur in >80% of pilocytic astrocytomas (von Deimling et al 2011). Furthermore, BRAF V600E mutations have been found most commonly in WHO grade II pleomorphic xanthoastrocytomas (66%) (Dias-Santagata et al 2011;Schindler et al 2011) as well as WHO grade I gangliogliomas (18%) (MacConaill et al 2009;Schindler et al 2011). In addition, Wu et al (2012) used wholegenome sequencing to identify recurrent mutations in H3FA, which encodes the H3.3 protein, and the closely related HIST1H3B gene, which encodes the H3.1 protein isoform, in pediatric diffuse pontine gliomas.…”
Section: The Genetic Basis Of Oligodendrogliomas and Pediatric Gliomasmentioning
confidence: 99%
“…BRAF rearrangements have also been identified in CNS tumors (Brastianos et al., 2014; Dias‐Santagata et al., 2011; Dougherty et al., 2010; Kleinschmidt‐DeMasters, Aisner, Birks, & Foreman, 2013; Koelsche et al., 2013, 2014). Very recently, the mutation V600E has been reported in 96% of papillary craniopharyngiomas (Brastianos et al., 2014).…”
Section: Introductionmentioning
confidence: 99%